The emerging roles of interstitial macrophages in pulmonary fibrosis: A perspective from scRNA-seq analyses - Gu, Yanrong; Lawrence, Toby; Mohamed, Rafeezul; Liang, Yinming; Yahaya, Badrul Hisham (Frontiers in Immunology, 2022)
Pulmonary fibrosis is an irreversible and progressive disease affecting the lungs, and the etiology remains poorly understood. This disease can be lethal and currently has no specific clinical therapeutic regimen. Macrophages, the most common type of immune cell in the lungs, have been reported to play a key role in the pathogenesis of fibrotic disease. The lung macrophage population is mostly composed of alveolar macrophages and interstitial macrophages, both of which have not been thoroughly studied in the pathogenesis of lung fibrosis. Interstitial macrophages have recently been recognised for their participation in lung fibrosis due to new technology arising from a combination of bioinformatics and single-cell RNA sequencing analysis. This paper reviews recent developments regarding lung macrophage classification and summarizes the origin and replenishment of interstitial macrophages and their function in pulmonary fibrosis.